Effects of topical application of Marantodes pumilum gel on the vagina of ovariectomized, sex steroid deficient rats / Nur-Amanina Syariff Tan - Nur-Amanina, Syariff Tan (2017)
Kacip Fatimah or Marantodes pumilum (MP) is known for its potential use as a herb to boost the women general well-being. Despite its widespread use, there is no scientific evidence which showed its beneficial effects in alleviating vaginal atrophy in the postmenopausal period. This study, therefore, intends to investigate the effects of MP on the vagina of post-menopausal rat model and possible mechanisms involved. Methods: Thirty-six female Sprague-Dawley (SD) rats were divided into six (6) groups (n=6) as follows: sham (ovariectomized), ovariectomized control (receiving plain vaginal gel treatment), ovariectomized, receiving MP at different concentrations (100 μg/mL, 250 μg/mL, and 500 μg/mL) and 0.005% estriol (E) topically for seven consecutive days. The rats were euthanized on the eighth day and vagina were then harvested for histological study and protein expression and distribution analysis by Western blotting and immunostaining, respectively. Vaginal ultrastructural changes were observed under transmission electron microscope (TEM) study. Results: Histological findings reveal dose-dependent increased in vaginal epithelial thickness following administration of MP. E treatment group had the thickest epithelia. An increase in the distribution and expression of cell proliferative proteins (PCNA and VEGF), tight junctional proteins (Occludin), water channel proteins (AQP-1 and AQP-2) and proton extruder proteins (VATPase A1) were observed in the vagina of MP and E-treated ovariectomized rats. TEM shows desmosome formation and approximation in intercellular space following treatment with 250 and 500 μg/mL MP and E. Conclusions: MP helps to alleviate vaginal atrophy in the sex steroid deficient state likely via inducing vaginal cell proliferation, promoting vaginal lubrication, improving vaginal acidity, and providing better intercellular integrity.